Composition dependence of structure, physical and mechanical properties of FeCoNi(MnAl)x high entropy alloys. (August 2017) - Li, Panpan; Wang, Anding; Liu, C.T.
Abstract: This paper has provided a systematic study of the crystal structure, physical and mechanical properties of FeCoNi(MnAl) x (0 ≤ x ≤ 2) high entropy alloys. As x increases, the crystal structure changes from FCC to FCC + BCC then to BCC solid solution. High saturated magnetization, low coercivity together with high electric resistivity are found in this system, indicating their potential applications as soft magnets. Meanwhile, the strength and hardness increase monotonously as x increases. Optimal balance of physical and mechanical properties are obtained in this system. Highlights: The structures, magnetic and mechanical properties of FeCoNi(MnAl) x high entropy alloy have been systematically studied. High saturated magnetization, low coercivity together with high electric resistivity are found in FeCoNi(MnAl) x alloy system. Optimal balance of physical and mechanical properties can be obtained in FeCoNi(MnAl) x alloy system.